2018
DOI: 10.1029/2018jb015568
|View full text |Cite
|
Sign up to set email alerts
|

Late Permian Bimodal Volcanic Rocks in the Northern Qiangtang Terrane, Central Tibet: Evidence for Interaction Between the Emeishan Plume and the Paleo‐Tethyan Subduction System

Abstract: Many studies provide compelling evidence for a fossil mantle plume beneath the Late Permian Emeishan large igneous province located near the southeastern margin of the central Tibetan Plateau, a region associated with the Paleo‐Tethyan subduction system. However, little is known about whether direct plume‐subduction interaction occurred during the Late Permian. Here we report geochronological, mineralogical, geochemical, and Sr‐Nd‐Hf‐O isotopic data for the Late Permian (~259–256 Ma) bimodal volcanic rocks (BV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 138 publications
2
10
0
Order By: Relevance
“…When a (sub) equatorial paleolatitude is observed, the choice between normal and reversed polarity is often ambiguous (Huang et al, ). The age of the middle part of our sampling section is dated at ~259 Ma, which is consistent with the age (~259–256 Ma) determined by SIMS U‐Pb zircon dating (Wang et al, ) and has reversed polarity (Ogg et al, ). Therefore, we concluded that our sampling area was more likely located at a paleolatitude of −7.6 ± 5.6°N at ~259 Ma.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…When a (sub) equatorial paleolatitude is observed, the choice between normal and reversed polarity is often ambiguous (Huang et al, ). The age of the middle part of our sampling section is dated at ~259 Ma, which is consistent with the age (~259–256 Ma) determined by SIMS U‐Pb zircon dating (Wang et al, ) and has reversed polarity (Ogg et al, ). Therefore, we concluded that our sampling area was more likely located at a paleolatitude of −7.6 ± 5.6°N at ~259 Ma.…”
Section: Discussionsupporting
confidence: 88%
“…They reliably show similar 206 Pb/ 238 U ages (Figure a), yielding a weighted average age of 259.1 ± 1.4 Ma with mean square weighted deviation = 0.77 (Figure b). The age of ~259 Ma determined by laser ablation sampling and multiple‐collector inductively coupled plasma mass spectrometry (LA‐MC‐ICPMS) dating method is well consistent with the secondary ion mass spectrometer (SIMS) U‐Pb zircon dating results (~259 Ma) for the same volcanic rock from the same bedding (Wang et al, ). Therefore, we confidently conclude that the Nayixiong Fm volcanics most likely erupted at ~259 Ma.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The resultant mantle flow gives rise to the deformation and stalling of the nearby mantle plume (Druken et al, ; Kincaid et al, ), such as in the Yellowstone (Northwestern United States) and Samoa (Southwest Pacific; Druken et al, ; Fletcher & Wyman, ). As a consequence, the slab‐driven mantle flow can entrain ocean island basalt (OIB)‐like enriched plume material and modify the chemistry of the mantle wedge in the subduction zone (Gazel et al, ; Obrebski et al, ; Price et al, ; J. Wang et al, ; Wendt et al, ). For example, the elevated helium isotopic ratios and high Nb concentrations (compared to other high‐field‐strength elements (HFSEs)) in the lavas from the Tonga arc system have been attributed as chemical inheritance from the nearby Samoa mantle plume (Ewart et al, ; Lupton et al, ; Price et al, ; Wendt et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…He et al, ; Y. Xu et al, ; Y. G. Xu et al, ). The Ailaoshan‐Red River shear zone was originally considered as the western boundary of ELIP (Y. X. Zhang et al, ), yet ELIP‐like basalts and mafic intrusions have been identified in Jinping (southern Ailaoshan region) in western Yunnan and Qiangtang terrane in Tibet (Chung et al, ; J. Wang et al, ; Xiao et al, ; Y. Xu et al, ) and northern Vietnam (e.g., Hoa et al, ), although whether there is any genetic link with the Emeishan plume is still debatable (Halpin et al, ). Paleozoic and Early Mesozoic magmatic rocks associated with the opening and closure of the Paleotethyan Ailaoshan Ocean were well documented in the western Ailaoshan volcanic belts (e.g., Fan et al, ; Jian et al, , ; Lai et al, ).…”
Section: Introductionmentioning
confidence: 99%